Bots, fake news, fake faces and deepfakes: automation, under the bias of dromology, as a sophisticated form of biopower to influence the democratic election process - Dias, Jefferson Aparecido (2021)
This article intends to examine, under the influx of technological advances, new forms of fake news, fake faces, and deepfakes that have been disseminated by social bots, among others, with the purpose to interfere in the electoral process. The methodology used was bibliographic and documentary research, consisting of the collection and analysis of information extracted from texts, books, and articles, in addition to other scientific data, such as reports, research, laws, and bills/ draft laws. Both biopower and biopolitics were used as theoretical references to contrast the collected data, whose approach is based on Michel Foucault and Antonio Negri’s studies, and also dromology, supported by Paulo Virilio’s studies. We concluded, using the deductive method, that the fake news massive dissemination by robots (bots), now humanized through fake faces and the dissemination of videos (deepfakes), can influence, modify the result of the election through the public opinion manipulation in the formation of its voting intention, which represents a serious violation of democracy and, therefore,urgent legal regulation and combat strategies are required.